Correlation of status of thyroid antibodies and thyrotropin hormone with prevalence of thyroid autoimmune disease in pregnancy - Mujawar, Shahid A.; Patil, Vinayak W.; Daver, Rekha G.; Mulkutkar, Sachin H. (International Journal of Research in Medical Sciences, 2018)
Background: Thyroid antibodies alterations were observed because of physiological and immunological changes occurring during pregnancy and after delivery. The aim was to evaluate serum anti-thyroid peroxidase antibodies (anti-TPO-Ab), anti-thyroglobulin antibodies (anti-TG-Ab) and total triiodothyronine (total T3), total thyroxine (total T4), thyrotropin hormone (TSH) levels in pregnant women of resident of Western India. Methods: Samples for 100 pregnant women with no apparent thyroid disorders were analyzed, using enzyme amplified chemiluminescent immune assay detection technology, in order to determine levels of total T3, total T4, TSH, anti-TPO-Ab and anti-TG-Ab in sera sample. Results: Of these women 24% gave biochemical evidence of hypothyroidism and remaining 76 % subjects were euthyroid in pregnant study group. In study group, 90% had normal values for anti-TPO-Ab and anti-TG-Ab and 10% had results revealing the presence of autoimmune diseases of the thyroid. Conclusions: n the present study, it was found that the level of anti-TG-Ab was found unaltered but it was found to be detected along with anti-TPO-Ab. These investigations should be performed routinely during pregnancy. Otherwise, lack of appropriate and early diagnosis and treatment can lead to neurological impairment of fetal brain as well as maternal cardiovascular diseases.